2019
DOI: 10.5433/1679-0359.2019v40n1p365
|View full text |Cite
|
Sign up to set email alerts
|

Metabolizable energy levels in diets with high lysine for growing and finishing pigs

Abstract: The objective of this experiment was to evaluate the effects of metabolizable energy (ME) levels in diets with high digestible lysine concentration on performance, carcass traits, and meat quality of barrows from 95 to 158 days of age. Eighty commercial hybrid barrows (50 ± 1.82 kg) selected for lean meat deposition, were assigned to four dietary treatments (3,150, 3,235, 3,320, and 3,400 kcal EM kg -1 ) in a randomized design with 10 replicate pens per treatment and two pigs per pen. From 95 to 116 days of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Therefore, our results may be explained by the lower level of dietary tryptophan; Liang et al (2018) have demonstrated that lower levels of tryptophan in the diet may lead to lower feed intake. Moreover, an optimal ratio between digestible lysine and metabolizable energy (ME) must be prioritized when the amino acid or energy contents of the diet change (Ferreira et al, 2019). Researchers have demonstrated that pigs present lower feed intake when fed lower SID lys:ME diets (Sweer et al, 2018;Ferreira et al, 2019), as might have been the case in the low-lys treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our results may be explained by the lower level of dietary tryptophan; Liang et al (2018) have demonstrated that lower levels of tryptophan in the diet may lead to lower feed intake. Moreover, an optimal ratio between digestible lysine and metabolizable energy (ME) must be prioritized when the amino acid or energy contents of the diet change (Ferreira et al, 2019). Researchers have demonstrated that pigs present lower feed intake when fed lower SID lys:ME diets (Sweer et al, 2018;Ferreira et al, 2019), as might have been the case in the low-lys treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The present study aimed to determine the response of pigs from the Chinese indigenous genotype to variables in the SID Lys level from 20 to 90 kg bodyweight and therefore estimate the optimal dietary SID Lys requirements of Baqing pigs at growth-finishing periods. Previous studies have clarified that Lys supplementation in the basal diet improved the growth performance and nutrient digestibility of growing and finishing pigs [ 24 , 25 ]. Similarly, Oresanya et al [ 26 ] illustrated that the BW and ADG of weaned pigs increased quadratically with increasing dietary Lys concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Grow-finishing pigs can compensate a low energy density diet by increasing ADFI [ 13 ]. However, there are inconsistencies regarding whether reducing dietary energy density results in a reduced [ 14 , 16 , 27 , 33 ] or similar energy intake [ 19 , 22 , 34 ]. If the energy value of feeds is correctly valued, and pigs can compensate for the reduced energy density, it would be expected that there would be no effect on ADG if there are no differences in maintenance energy requirements [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…2, De La Llata et al [ 37 ] only reported an effect of increasing energy density in the first growing phase (25–45 and 34–60 kg BW, for gilts and barrows, respectively), but it was not significant for later phases up to 120 kg BW. Other authors did not report an effect of reducing dietary NE on daily NE intake [ 19 , 34 , 40 ]; however, Beaulieu et al [ 22 ] reported effects when research was carried out in research facilities but not in commercial farms. It is possible, as suggested by Nitikanchana et al [ 25 ], that there is an extra value of adding fat to a diet in addition to its high energy content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation